Prophylactic Retrorectus Mesh Versus Small-Stitch Closure After Emergency Midline Laparotomy: 2-Year Results of a Randomized Controlled Trial - Mäkäräinen, Elisa; Tolonen, Mari; Sallinen, Ville; Mentula, Panu; Leppäniemi, Ari; Ahonen, Matti; Saarnio, Juha; Pinta, Tarja; Lampela, Hanna; Malmi, Hanna; Lietzen, Elina; Nikki, Marko; et al. (Frontiers Media SA, 2026)
Introduction:
Incisional hernias (IH) are common complications following emergency midline laparotomies. Mesh reinforcement has shown efficacy in preventing incisional hernias in elective surgeries, but evidence remains limited for emergency midline incisions. This study aimed to evaluate the safety and effectiveness of retrorectus placement of a self-gripping polyester mesh in preventing incisional hernia after emergency midline laparotomy, as measured by the incidence of IH, postoperative complications, quality of life, and health economic outcomes.
Methods:
In this multicenter randomized controlled trial, adult patients undergoing emergency midline laparotomy were randomized to receive either prophylactic retrorectus mesh or standard 4:1 small-stitch fascial closure using a slowly absorbable monofilament suture. The primary outcome was the radiological/clinical IH rate within 2 years after the surgery. Secondary outcomes were complications, reoperations, quality of life, and health-economic measures. Blinding was maintained for patients, outcome assessors, and radiologists. Due to difficulties in recruitment, the study was prematurely terminated prior to reaching the aimed number of patients.
Results:
Out of 925 patients screened, 109 were randomized, and 72 received the allocated intervention. At 2-year’s follow-up, one (4%) asymptomatic incisional hernia was detected in the control group compared to none in mesh group. In the mesh group, three (9%) patients experienced mesh-related complications: one (5%) retrorectus hematoma, one (5%) internal hernia and one (5%) postoperative seroma. One (5%) additional patient in the mesh group developed a fistula requiring mesh removal. No significant differences were found in early postoperative complications or quality of life between groups.
Conclusion:
Retrorectus mesh reinforcement did not reduce the incidence of incisional hernia compared to standard small-stitch closure in this trial. However, mesh-related complications were observed. Due to recruitment challenges and limited sample size, definitive conclusions cannot be drawn.